Haïti - Untitled ; Dreamers - Leth, Jorgen; Holmberg, Dan; Gruszynski, Alexander; Tengberg, Bo (Danish Film Institute, 2008)
Haïti - Untitled (1996): Writer and cineaste Jørgen Leth is the fascinated observer of a country where reality often seems surreal and resembles fiction. Haiti’s history is written in blood. Voodoo plays an important role in politics. Death and horror are part of Haiti’s everyday life. Leth and his crew have witnessed dramatic events in the past 5 years, but he has also captured moments of sensuality and beauty in his epic and very personal documentary. [www.docreview.pl]
Keywords: DVD-Video